Reaching for Health Equity and Social Justice in Baltimore: The Evolution of an Academic-Community Partnership and Conceptual Framework to Address Hypertension Disparities - Cooper, Lisa A. (Ethn Dis, 2016)
Cardiovascular health disparities persist despite decades of recognition and the availability of evidence-based clinical and public health interventions. Racial and ethnic minorities and adults in urban and low-income communities are high-risk groups for uncontrolled hypertension (HTN), a major contributor to cardiovascular health disparities, in part due to inequitable social structures and economic systems that negatively impact daily environments and risk behaviors. This commentary presents the Johns Hopkins Center to Eliminate Cardiovascular Health Disparities as a case study for highlighting the evolution of an academic-community partnership to overcome HTN disparities. Key elements of the iterative development process of a Community Advisory Board (CAB) are summarized, and major CAB activities and engagement with the Baltimore community are highlighted. Using a conceptual framework adapted from O’Mara-Eves and colleagues, the authors discuss how different population groups and needs, motivations, types and intensity of community participation, contextual factors, and actions have shaped the Center’s approach to stakeholder engagement in research and community outreach efforts to achieve health equity.